HUBUNGAN KEGEMUKAN DENGAN KONSEP DIRI PADA REMAJA USIA 16-18 TAHUN (Studi Analitik Di SMA Negeri 2 Pare) - Susilowati, Susilowati (Akademi Keperawatan Pamenang, 2011)
Self concept is the way individuals view themselves in their entirety. As with adolescents who are overweight, obesity directly affects their physical and can not be denied that its appearance can affect how individuals view themselves and ultimately will affect the self-concepts in adolescents. The purpose of this study is to determine the relationship of obesity with self-concept in adolescents aged 16-18 years.The research method is correlational analytic with Cros-Sectional approach. Population of the study was 38 students, the sample was 33 respondents, the sampling technique used was purposive sampling. Data presented in the form of pie charts, tables and cross tabulation.Data from this study indicated that out of 33 respondents who researched, adolescents who are overweight with negative self-concept was 19 respondents (57.6 %). Adolescents who experience positive self-concepts was 14 respondents (42.4 %). based on the results of correlation test, p valuewas = 0,012 (bellow than Â Â = 0.05) , means that there is a significant relationship between overweight self-concept on youth which is positive and moderate (contingency coefficient 0.401).This above at possible because teens are overweight, so a negative selfÂ concept, so that adolescents have a positive self-concept adolescents should be active in both school, and at home like hanging out with teens youth clubs, following the instruction in the schools involved to exercise extra-curricular can forge good relationships with others so as to create a positive self-concept.